Effects of protein levels and withdrawing supplemental protein on performance of growing and finishing steers - Harrison, K.F.; Fink, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
one growing trial and two finishing trials we used 264 steers. Rations containing 13.2% crude protein during the 105-day growing trial significantly (P<.05) improved rate of gain gain compared with 11.3% crude protein rations. Withdrawing supplemental protein at approximately 750, 850, or 950 pounds live weight did not significantly affect rate of gain; however, gain was slowest by steers without supplemental protein.
Keywords: Beef; Protein; Steers; Gain